Clinical validation of cutoff target ranges in newborn screening of metabolic disorders by tandem mass spectrometry: a worldwide collaborative project - McHugh, D.M. (2012)
To achieve clinical validation of cutoff values for newborn screening by tandem mass spectrometry through a worldwide collaborative effort